2000
DOI: 10.1002/j.2162-6057.2000.tb01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Concepts of Creativity: Similarities and Differences among Mainland, Hong Kong and Taiwanese Chinese

Abstract: Aspects of creativity concepts across different Chinese populations were examined. A Likert style questionnaire consisting of 60 adjectives was administered to 451 undergraduates from Beijing, Guangzhou, Taipei and Hong Kong. The results show that: (a) the core characteristics of creativity identical in all the samples are: “originality”, “innovativeness”, “thinking” and “observational skills”, “flexibility”, “willingness to try”, “self confidence”, and “imagination”; (b) the Taipei sample, unlike the other th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
94
1
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 9 publications
9
94
1
4
Order By: Relevance
“…Most cross-cultural work that contrasts perceptions of creativity emphasizes which concepts are most associated with creativity. For example, Westem conceptions tend to emphasize unconventionality, inquisitiveness, imagination, humor, and freedom (Murdock & Ganim, 1993;Stemberg, 1985), Eastern conceptions are more likely to encompass moral goodness, societal contributions, and connections between old and new knowledge (Niu & Stemberg, 2002;Rudowicz & Hui, 1997;Rudowicz & Yue, 2000), It would be interesting to see how these different cultures view creativity by domain, Cheung and Yue (2007) found that Chinese students viewed scientists as more creative than other professions. Such comparable preferences and beliefs may result in different pattems for different cultures.…”
Section: Discussionmentioning
confidence: 97%
“…Most cross-cultural work that contrasts perceptions of creativity emphasizes which concepts are most associated with creativity. For example, Westem conceptions tend to emphasize unconventionality, inquisitiveness, imagination, humor, and freedom (Murdock & Ganim, 1993;Stemberg, 1985), Eastern conceptions are more likely to encompass moral goodness, societal contributions, and connections between old and new knowledge (Niu & Stemberg, 2002;Rudowicz & Hui, 1997;Rudowicz & Yue, 2000), It would be interesting to see how these different cultures view creativity by domain, Cheung and Yue (2007) found that Chinese students viewed scientists as more creative than other professions. Such comparable preferences and beliefs may result in different pattems for different cultures.…”
Section: Discussionmentioning
confidence: 97%
“…Another related and unanticipated finding is that academic and leadership have higher correlations than creativity does with music and art final exam scores. Some researchers indicate that the Chinese concept of creativity is different from the Western concept (Rudowicz & Hui, 1998;Rudowicz & Yue, 2000). Creativity may not be regarded as a highly desirable characteristic for a Chinese student to possess and it may not be considered a type of giftedness in China (Rudowitz & Yue, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Torrance (1962) found that developmental patterns of creativity differed across cultures; Arab students score consistently higher on creativity in figural tests than American participants (Mar'i & Karayanni, 1983); there are differences and similarities in the importance of novelty and appropriateness to creativity between Chinese, Japanese, and Americans that run counter to stereotypes (although not between Asian Americans and Caucasian Americans; Paletz & Peng, 2008); and although not compared directly with American samples, several studies suggest that lay theories of creativity and personality are different between Westerners and various Chinese groups (e.g., Rudowicz & Hui, 1997;Rudowicz & Yue, 2000). Only future research can answer these questions.…”
mentioning
confidence: 96%